Mechanisms For Ensuring Spiritual Security - Umidjonovich, Nurullaev (Academicia Globe: Inderscience Research, 2025)
Spiritual security is connected with the ideals, first of all, of a spiritual, moral and ethical order. They determine not only the value priorities of the life of the whole society, but also the fixed positive forms of their reproduction, transmission and preservation as a shrine in all manifestations of the life of the people. Spiritual security presupposes, first of all, the preservation of people's lives in their human, not animal, quality. The threat posed against human morale is gaining more impact power compared to armed attacks. Therefore, in order to avoid such threats, the direction of spiritual security is prioritized in protecting the interests of members of society in any country that sets itself the goal of ensuring the stability of national development. In this article highlights of means spiritual security, it’s importance in the upbringing of youth and mechanisms in the development of society.